Refugees and Migrants: The Influence of False News in the Media and Perception of Society - Aleksandrova, Svetla (Research Papers, 2022)
The last decade has been marked by several waves of migration related to the military conflicts and wars. The consequences caused by these waves often were named as “crisis”. The aim of the paper is to find the successful measures against the spread of fake news and offensive media coverage by studying the experience of European countries. The comparative analysis of Eurostat data on migration flows and Eurobarometer public opinion surveys will be applied as an indicator for successful social campaigns. Examples can be given of good European practices for ensuring the resilience of fake news and misinformation for migrants and refugees.